INTELLECTUAL DEVELOPMENT AND CHARACTERISTICS OF SPEECH IN CHILDREN WITH AUTISM (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This article provides information about intellectual development and the uniqueness of speech in children with autism. The possibilities of intellectual development of children with autism are different: from mental retardation to mild retardation of mental development and the development of a specific manifestation of knowledge processes in a certain field as talent.